HUNTER-GATHERER LAND USE STRATEGIES AND HAND STENCILS IN SOUTHERN PATAGONIA: A COMPARATIVE ANALYSIS OF THE STROBEL PLATEAU AND CARDIEL LAKE (ARGENTINA) - Guichón, Francisco; Re, Anahí (Revista Cuadernos de Arte Prehistorico, 2021)
Southern Patagonia rock art is characterized by the presence of a large number of hand stencils with a wide distribution. The general aim of this paper is to contribute to the study of spatial trends in hand stencil production in this region and its relationship with different land use strategies carried out by hunter-gatherer groups. Here we explore the contribution that the study of this particular rock art motif may have to understanding the demography of the human groups that occupied the area. In particular, rock art from the Cardiel Lake low basin and the Strobel high plateau located in the province of Santa Cruz, Argentina, is analysed. Current research suggests that these two areas were occupied intensively and in a complementary way in the last 2,500 years (Late Holocene). While the Cardiel Lake basin would have been mainly used for residential purposes year-round, the Strobel Plateau occupations would have been logistic and seasonal. The results obtained make it possible to identify the greatest importance of hand stencils in the rock art of Cardiel basin. On the other hand, the participation of all age groups is evident in the production of this type of motif, both in the low basin and the Strobel Plateau. The latter fact complicates the previously proposed panorama and raises a new series of questions for archaeological research.